EMPOWERING THE COMMUNITY PROTECTION UNIT MEMBERS BY THE COMMUNITY PROTECTION TASK FORCE OF TANAH BUMBU DISTRICT, SOUTH KALIMANTAN PROVINCE - Yogaswara, Adrian Rianda; Rukmana, Maris Gunawan (Fakultas Hukum Tata Pemerintahan, 2024)
The rapid development of information technology brings new challenges in maintaining public security and order. The Community Protection Unit (Satlinmas) in Tanah Bumbu Regency needs to improve its effectiveness in facing these challenges, in terms of ability, expertise, and knowledge. This research qualitatively analyzed efforts to empower Satlinmas members in Tanah Bumbu Regency based on Sumadyo’s theory, which consists of Business, Human, Environmental, and Institutional Development aspects, with an inductive approach. The research results showed that the empowerment efforts made have covered several aspects but still face a number of obstacles. Limited budget, lack of synergy between institutions, low community participation, and minimal infrastructure are the main inhibiting factors in increasing the capacity of Satlinmas members. To improve empowerment results, it is recommended to further encourage village governments to use village budget and funds, further socialize community protection, strengthen the synergy between the Community Protection Task Force and Satlinmas, and provide allowances and insurance for Satlinmas members. Keywords: Empowerment; Community Protection Unit Members; Community Protection Task Force of Tanah Bumbu Regency.